Influencia del pH y el tiempo de contacto en el porcentaje de remoción de Pb²+ y Cd²+ en soluciones acuosas, utilizando zeolitas tipo clinoptilolita modificada con MgCl2 - Guevara Neyra, Jhonny (2017)
Using the Clinoptilolite type of Zeolite modified with Magnesium Chloride, the influence of pH and exposure time on the percentage of removal of Pb2+ and Cd2+ in aqueous solutions in a closed system, was determined. The zeolites provided from Ecuador, were washed with deionized water and dried at 350°C to remove water from the interior of the structure, then the modification was carried out with Magnesium Chloride in a ratio by weight of MgCl2 / Zeolite = 2.5. The purpose of the modification was to increase the pore diameter and the surface area of the zeolite and thus obtain improved results. With the modified zeolite, adsorption tests were carried out, obtaining the highest percentage of removal of Pb2 + "97%" at a pH = 4 over a time of 180 min. For Cadmium the same trend was observed with pH, but the time at which the zeolite was saturated was 40 min, thus obtaining 77% Pb2 + removal at a pH = 4 over a time of 40 min. For comparison, adsorption tests were also carried out using natural zeolite; it was determined that the percentage of Pb2 + removal with the modified zeolite was 1.7 and 1.6 times higher than that obtained with natural zeolite for lead and cadmium, respectively. Statistical analyses demonstrate that there are significant differences between the percentages of lead removal obtained at different pHs, while for Cadmium there were no significant differences in the percentages of its removal. In comparing the percentages of Pb2+ removal obtained by modified zeolite and natural zeolite at different pHs, it was determined that there are significant differences in all cases, from which it is concluded that the modification of the zeolite for lead removal is viable